Advances in accounting behavioral research. Vol. 19 - Karim, Khondkar E., 1961-; Fogarty, Timothy (Bingley, U.K. : Emerald, 2016)
Advances in Accounting Behavioral Research publishes high-quality research encompassing all areas of accounting including financial, auditing, taxation, managerial and information systems, addressing a broad range of issues that affect the users, preparers and assurers of accounting information. Further, this research incorporates theory from, and contributes knowledge and understanding to, applied psychology, sociology, management science, and behavioral economics.
An analysis of the research contributions of advances in accounting behavioral research: 1998-2012 / Daryl M. Guffey -- The new normal? enhanced psychological well-being from public accounting: mitigating conflict with flexibility and role clarity / Ambrose Jones, III, Cynthia P. Guthrie -- Are investors influenced by accounting presentation format and announcement prominence of special items? / Lei Dong, Bernard Wong-On-Wing, Gladie Lui -- Accounting guidance flexibility, auditors' ethical characteristics, and blame / Robert M.cornell, Rick C.warne -- An empirical examination of psychological climate and internal disclosure policy compliance / Randall Young.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Accounting -- Financial; Accounting; Finance & accounting; Accounting; Accounting -- Psychological aspects